A new model for the segmentation, propagation and linkage of the Tan-Lu fault zone, East Asia. (January 2023) - Li, Chengming; Zhang, Changhou; Cope, Tim D.
Graphical abstract: Highlights: The Tan-Lu Fault formed by coalescence of two kinematically independent segments. The northern and southern Tan-Lu faults exhibit contrasting displacement profiles. The northern and southern Tan-Lu faults propagated in opposite directions. Southward indentation of the Siberian craton initiated the northern Tan-Lu Fault. The northern and southern Tan-Lu faults linked in the early Late Jurassic. Abstract: The Tan-Lu fault zone (TLF) is a major strike-slip fault with a long and complex history in East Asia, whose evolution provides a new perspective on the formation of large-scale faults (>1000 km long). Fault displacement analysis, geological mapping and U-Pb LA-ICP-MS dating have been performed to understand the evolution of the TLF. Along-strike displacement variation reveals that the TLF consists of two kinematically independent segments, the northern and southern TLF, with opposite long-term propagation directions. Structural and geochronological studies in the eastern Yanshan belt, located around the linkage area of the southern and northern TLF, indicate that NNE-trending sinistral strike-slip faults initiated at 167–164 Ma and were reactivated at 124–121 Ma. Structural analysis suggests that these early NNE-trending strike-slip faults transferred sinistral motion along the northern TLF into southward thrusting along the Yanshan belt, representing the Middle Jurassic southern termination of the northern TLF. Our studies suggest that the through-going TLF formed when the younger southward-propagating northern TLF merged with the older northward-propagating southern TLF in the Late Jurassic. A new model is thus proposed for the Mesozoic evolution of the TLF. The initiation and southward propagation of the northern TLF is interpreted to have resulted from the southward indentation of the Siberian craton into the amalgamated Central Asian Orogenic Belt and North China block. The divergent mega-splays of the northern TLF likely resulted from westward-younging formation during the clockwise rotation of northeast Asia. Coalescence of two genetically unrelated faults could be an alternative mode for large-scale fault formation.